Genetic Analysis of Aromatic and Quality Rice Germplasm using Microsatellite Markers - Shams, F.D.; Kuddus, M.M.A.; Nasiruddin, K.M.; Begum, S.N.; Islam, M.M. (Plant Tissue Culture and Biotechnology, 2012)
Twenty rice genotypes were analysed with three SSR primers viz., RM223, RM515 and RM342 for detection of the fgr gene responsible for aroma. The primers RM223 and RM515 identified eight and seven genotypes, respectively as having the fgr locus. Presence of the specific allele of the RM342 amplicon, also correlated with strong aroma in two and with weak aroma in five genotypes. The banding pattern for the primer RM342 was different in genotypes with no aroma. Among the three primers (RM223, RM515 and RM342), RM223 detected the highest number of fgr loci in the 20 rice genotypes. In total 11 genotypes were identified as having strong aroma genes by the three primers. These accessions also showed high yields and therefore may prove to be a good source for producing aromatic rice. DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11262 Plant Tissue Cult. & Biotech. 22(1): 65-71, 2012 (June)